IMPROVING THE THINKING OF THE YOUTH OF A NEW UZBEKISTAN READING CULTURE SOCIAL-PHILOSOPHICAL THOUGHTS ON PLACE - Abdulwohid Abdulazizov (Web of Journals Publishing, 2025)
The article presents the author's socio-philosophical point of view on the problems of developing a reading culture that are relevant in society today, and discusses the importance of reading among the youth of New Uzbekistan. culture event processes condition objective analysis It has been emphasized that the attention to reading in Uzbekistan is inherited from our ancestors, and the phenomenon of reading is one of the least studied areas. one is, especially students and young people reading culture to shape issue whole research object as less unexplored A conclusion is given.
Keywords: Theoretical aspects of reading, universal human values, reading phenomenon, general theory of reading, category of reading “book”, problems of reading, hypothesis, harmony of approaches.